Beyond toxicity: Systems-level virulence of entomopathogenic fungi in termite social immunity - Hafiz Muhammad Usman; Hammad Hassan; Arshad Ali; Mohammad Mazharul Karim; Ali Hassan; Min Lu (Journal of Invertebrate Pathology, 2026)

Engineering MOF-on-MOF heterostructure for enhanced adsorption-assisted photocatalytic decontamination of carbamazepine: Kinetics, thermodynamic and pathway study - Muhammad Fayaz; Raza Ullah; Muzamil Ahmad; Ikram Ullah; Muhammad Rafiq; Ali Ahmad; Nasim Ullah; Faizan Jamil; Latif Ur Rehman; Hammad Ali; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2026)

Effect of predatory pressure on behavior of termite Reticulitermes chinensis - Hammad Hassan; Ali Hassan; Taqi Raza; Hafiz Muhammad Usman; Arshad Ali; Jinli Ding; Qiuying Huang; Min Lu (Journal of Insect Physiology, 2026)

Seroprevalence and risk factors of Mycobacterium avium subsp. paratuberculosis in dromedary camels of Southern Punjab, Pakistan - Aliza Ali; Mughees Aizaz Alvi; Muhammad Hammad Hussain; Muhammad Numan; Junaid Ahmad; Muzafar Ghafoor; Muhammad Khalid Mansoor; Muhammad Saqib (Tropical Animal Health and Production, 2026)

Bridging iron biofortification through integrative strategies from QTL mapping to regulatory-compliant genome editing - Sadia Hakeem; Safia Khushi; Muhammad Hammad Nadeem Tahir; Nadia Hussain Ahmed; Amna Bibi; Zulfiqar Ali (Cereal Research Communications, 2026)
Around two billion people are affected by iron (Fe) malnutrition globally, largely contributed by the consumption of cereal-based diets with low levels of iron and reduced bioavailability due to presence of inhibitor compounds like phenols and phytic acid. Among several methods of enhancing Fe content of staples, genetic biofortification is the most sustainable, and cost-effective method. Genetic biofortification through conventional breeding has succeeded in producing a number of cultivars marketed for high nutrition. However, this approach is limited due to the requirement of large genetic variation, long breeding time, phyto-availability of nutrients through soil only, gene targeting in compatible species only, lack of knowledge of QTL and genetic maps, environmental interactions, risk of linkage drag, and complex interrelations among nutrients as well as with other yield traits. With the advent of genomic approaches for targeted genetic manipulation, transgenic approach offers straightforward and robust techniques to genetically biofortify staples. While transgenic approaches to increasing Fe content have been helpful, genetically modified (GM) cultivars for staple crops may be delayed due to GM regulatory barriers. This chapter reviews the global status of Fe malnutrition, possible solutions to combat its deficiency, and bottlenecks towards Fe biofortification in staples. It also provides insights into transgenic approaches to address this issue as well as way forward to resolve the regulatory issues associated with GM crops by providing alternate options.

Paleocene stratigraphic framework and sedimentary architecture in the Sub-Himalayan Fold and Thrust Belt of Muzaffarabad, Pakistan: Depositional environment, Biotas, Paleogeographic and Economic Significance - Syed Kamran Ali; Arslan Sajjad; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Aamir Asghar; Aijaz Ali Halepoto; Evangelia Besiou; Assimina Antonarakou (Journal of Sedimentary Environments, 2026)

Insecticidal and antibacterial potential of Croton tiglium functionalized zinc oxide nanoparticles - Arshad Ali; Ali Hassan; Imran Afzal; Hammad Hassan; Kirshan Chand; Hafiz Muhammad Usman; Xiaolong Liu; Min Lu (International Journal of Tropical Insect Science, 2026)

Competitive adsorption of antibiotics on waste-derived hybrid biochar: Performance, mechanism, and life cycle assessment - Ali Hamid; Ahsan Jalal; Muhammad Arshad; Muhammad Usama; Sajjad Hussain; Hammad Khan (Journal of Environmental Chemical Engineering, 2026)

Synergistic NiO-Pt heterostructure for enhanced hydrogen evolution: Boosting charge transfer and catalytic efficiency in alkaline media - Faria Rafique; Shahzad Ameen; Muhammad Hammad Ali; Aleena Tahir; Hamayal Shahzad; Amina Bhatti; Tanveer ul Haq; Mira Tul Zubaida Butt; Ammar Ahmed Khan; Saleh A. Ahmed; Irshad Hussain; Habib Ur Rehman (Fuel, 2026)

From half-cells to full-cells: across-scale comparative evaluation of lanthanum-based perovskites as high-performance anode materials for the oxygen evolution reaction - Blaž Toplak; Leon Müller; Ali Raza Khan; André Olean-Oliveira; Khuzaifa Yahuza Muhammad; Wang Feng; Raíssa Ribeiro Lima Machado; Da Xing; Mohammed-Ali Sheikh; Leander Kucklick; Ahammed Suhail Odungat; Adarsh Jain; et al. (Chemical Engineering Journal, 2026)

Sustainable biodiesel production via Alkanna tinctoria oil Conversion: A multi-method modeling approach utilizing crab shell-derived biochar catalysts - Ali Hamid; Hammad Khan; Arsalan Arif; Muhammad Arshad; Sajjad Hussain; Arslan Maqbool (Biomass and Bioenergy, 2025)

Prediction of RNA editing sites and genome-wide characterization and identification of PERK gene family in Oryza sativa in response to salinity stress - Hafiz Muhammad Waqas; Muhammad Abu Bakar Saddique; Sajid Fiaz; Afnan A. Alnufaei; Muhammad Ali Sher; Badr Alharthi; Muhammad Hammad Nadeem Tahir; Mahmood Alam Khan; Shahmeer Shahid; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2025)

Dolomitized stromatolites during regressive-transgressive cycles in the Cambrian Abbottabad Formation, Pakistan: depositional environment, sequence stratigraphic significance, and paleogeographic implications - Syed Kamran Ali; George Kontakiotis; Tariq Mahmood; Muhammad Saleem Mughal; Hammad Tariq Janjuhah; Ahmer Bilal; Evangelia Besiou; Assimina Antonarakou (Carbonates and Evaporites, 2025)

Comprehensive study on efficient diclofenac sodium removal using walnut and pistachio shell activated carbon: ANN, kinetics, isotherms, thermodynamics and DFT calculations - Sinem Temiz Seymen; Handan Atalay Eroğlu; Elif Nihan Kadıoğlu; Muhammad Umar; Ali Hamid; Hammad Khan; Sajjad Hussain; Feryal Akbal (Biomass and Bioenergy, 2025)

Sustainable wastewater treatment via nitrogen/sulfur co-doped graphene composite: Mechanistic insights & process optimization - Humaira Seema; Muhammad Arshad; Arslan Maqbool; Sumbal Zeb; Ali Hamid; Muhammad Umar; Sajjad Hussain; Hammad Khan (Journal of Water Process Engineering, 2025)

Adsorption of 4-bromophenol from simulated wastewater using magnetic carbon-based composites: Kinetics, equilibrium, thermodynamics, and density functional theory analysis - Beatris L. Mello; Pascal S. Thue; Ali Hamid; Muhammad Usama; Fernando Machado Machado; Moaaz K. Seliem; Younes Dehmani; Glaydson S. dos Reis; Mohamed Abdel Salam; Hammad Khan; Luis F.O. Silva; Eder C. Lima (Journal of Water Process Engineering, 2025)

Macroalgae Polysaccharides Enhance Brain Health by Mitigating Scopolamine-induced Oxidative Stress and Inflammation Via Nrf-2/TLR4/NF-kB Pathways - Zahir Shah; Arshad Iqbal; Syed Lal Badshah; Mushtaq Ahmad Mir; Saima Sohni; Hammad Ullah; Shahid Ali Shah; Nasreena Bashir; Muhammad Ayaz; Maria Daglia (Journal of Neuroimmune Pharmacology, 2025)

Importance of an Oncology Interest Group in Medical School: Experience from a Developing Country - Hammad Atif Irshad; Abdul Rehman; Muhammad Ali Akbar Khan; Dahir Ashfaq; Munira Moosajee (Journal of Cancer Education, 2025)

Performance and data acquisition from low-cost air quality sensors: a comprehensive review - Mubashir Ali Siddiqui; Mirza Hammad Baig; Muhammad Uzair Yousuf (Air Quality, Atmosphere & Health, 2025)

Effect of resveratrol on post-thaw motility, kinematics, structural parameters and antioxidant/oxidant status of Kamori buck spermatozoa - Tarique Hussain; Muhammad Hammad Fayyaz; Amjad Hameed; Syed Murtaz Hassan Andrabi; Rehana Kausar; Yasin Mubashir; Iqra Batool; Muhammad Shahzad; Ali Dogan Omur (Cryobiology, 2025)

Effects of dietary organic selenium, vitamin C, and vitamin E supplementation on growth performance, serum biochemistry, and antioxidant status in juvenile Hypophthalmichthys molitrix - Hairui Yu; Maida Mushtaq; Saira Razzaq; Umar Ali; Muhammad Khan; Abdur Rahman; Guobo Quan; Mehroze Fatima; Saima Naveed; Muhammad Hammad Zafar; Muhammad Aziz ur Rahman (Frontiers in Marine Science, 2025)
The study aimed to evaluate the effects of dietary supplementation of selenium (Se), vitamin C, and vitamin E on growth performance, meat quality, and antioxidant status in Hypophthalmichthys molitrix juveniles. A total of 480 juveniles (mean weight: 20 ± 0.29 g) were randomly assigned to 24 aquaria (20 fish per 100 L), which were allocated to eight dietary treatments (three aquaria per treatment) following a completely randomized design. The dietary treatments included: (1) a basal diet without supplementation (Control), (2) selenium supplementation (S), (3) vitamin C supplementation (C), (4) vitamin E supplementation (E), (5) selenium and vitamin C supplementation (SC), (6) selenium and vitamin E supplementation (SE), (7) vitamin C and vitamin E supplementation (EC), and (8) selenium, vitamin C, and vitamin E supplementation (SCE). The supplementation levels were 0.9 mg/kg Se, 300 mg/kg vitamin C, and 100 mg/kg vitamin E, respectively. After a one-week acclimatization period, a 10-week growth trial was conducted. Fish fed the SCE diet exhibited significantly higher (p< 0.05) final weight gain, body length gain, body weight gain percentage, and specific growth rates compared to other treatments. Selenium concentrations in the kidney, liver, pancreas, and muscle were significantly higher (p< 0.05) in the SCE, SC, SE, and EC groups compared to the Control and single-supplement groups. Hematological parameters, including WBC, RBC, HGB, HCT, and MCHC, were significantly higher (p< 0.05) in the SCE group compared to all other groups. Similarly, serum activities of ALT, AST, and ALP were significantly lower (p< 0.05) in the SCE group than in other treatments, while blood glucose levels were unaffected (p > 0.05) by dietary treatments. Antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were significantly enhanced (p< 0.05) in the whole body and muscle tissues of fish receiving Se, vitamin C, and E supplementation. Thiobarbituric acid reactive substances (TBARS) levels in muscle and serum were significantly higher (p< 0.05) in the Control group compared to all supplemented groups. The proximate composition of meat, including dry matter, fat, ash, and protein contents, was not significantly affected (p > 0.05) by the dietary treatments. In conclusion, dietary supplementation of selenium, vitamin C, and vitamin E significantly improved growth performance, selenium deposition in tissues, and antioxidant status of Hypophthalmichthys molitrix juveniles, without adversely affecting meat chemical composition.

From pollutant to purifier: Leveraging plastic waste-derived activated carbon for sustainable water remediation solutions - Hammad Khan; Muhammad Usama; Mohammad Ilyas Khan; Fazal Wahab; Izhar Ahmad; Ali Hamid; Sajjad Hussain; Arslan Maqbool (Journal of Environmental Management, 2025)

Bio-catalytic activity of novel poly(ethylene glycol) methacrylate hybridized silver nanomaterials - Natasha Anwar; Mohib Shah; Saad Haroon Anwar; Muhammad Ishaq Ali Shah; Amir Zada; Hammad Ahmad Jan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (South African Journal of Botany, 2025)

Unveiling the biosorption performance of silk fibroin fiber for Pb(II) and Cr(VI) removal: Machine learning and DFT analysis - Muhammad Usman Farooq; Hammad Khan; Muhammad Arshad; Muhammad Usama; Mohammad Ilyas Khan; Sajjad Hussain; Ali Hamid (Journal of Water Process Engineering, 2024)

Utilizing Cinnamomum verum (a culinary spice), as a functional food ingredient ameliorating hypercholesterolemia: In-vivo, in-vitro, and in-silico multi-model analysis - Mahnoor Bano; Muhammad Khurram Waqas; Talha Ali Chohan; Fakhra Batool; Aamir Mushtaq; Yahya I. Asiri; Mohd. Zaheen Hassan; Md Ali Mujtaba; Md. Khalid Anwer; Muhammad Irfan Sidique; Ayesha Riaz; Umair Khurshid; et al. (Food Bioscience, 2024)

The interplay of PTEN and AKT nexus in breast cancer: a molecular perspective - Anum Kamal; Ali Raza Awan; Masood Rabbani; Hammad Raza Sheikh; Muhammad Tayyab; Sehrish Firyal; Imran H. Khan; Muhammad Wasim (Molecular Biology Reports, 2024)

Nutritional and medicinal plants as potential sources of enzyme inhibitors toward the bioactive functional foods: an updated review - Hammad Saleem; Anam Yaqub; Rabiya Rafique; Tahir Ali Chohan; Durr-e-Shahwar Malik; Muhammad Imran Tousif; Umair Khurshid; Nafees Ahemad; Ramasamy Ramasubburayan; Kannan RR Rengasamy (Critical Reviews in Food Science and Nutrition, 2024)

The Cambrian sedimentology and reservoir properties of the hybrid Abbottabad Formation in the Kotli area, Sub-Himalaya, Pakistan: insights into the Proto-Tethys paleoenvironment - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Tariq Mahmood (Carbonates and Evaporites, 2024)

Assessing Asiatic black bear (Ursus thibetanus) temporal overlap and co-occurrence with sympatric species in the temperate zone of the Hindu Raj Mountain range - Faizan Ahmad; Muhammad Rehan; Eve Bohnett; Ammar Hassan; Sami Ullah; Shah Zeb; Hammad Ali Mian; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Socio-environmental factors and solar housing system adoption: moderating effect of attitude - Ahsen Maqsoom; Muhammad Hammad; Muhammad Umer; Wesam Salah Alaloul; Hassan Ashraf; Muhammad Ali Musarat; Tahira Nazir (Innovative Infrastructure Solutions, 2024)

Synthesis and characterizations of conocarpus- and azadirachta-derived activated carbons as wastewater recycling material - Murtuza Mehdi; Mirza Hammad Baig; Masood Ahmad; Kamran Ali; Muhammad Mohib; Ali Farooqi; Mohammad Affan; Muhammad Mazin (Environmental Monitoring and Assessment, 2024)

Effect of riboflavin on redox balance, osmolyte accumulation, methylglyoxal generation and nutrient acquisition in indian squash (Praecitrullus fistulosus L.) under chromium toxicity - Habiba Kanwal; Syed Hammad Raza; Shafaqat Ali; Muhammad Iqbal; Mudassir Iqbal Shad (Environmental Science and Pollution Research, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

A decline in snow cover area of Passu and Ghulkin valleys between 1995 and 2022 - Imran Hussain; Mumtaz Ali; Sher Muhammad; Wajid Hassan; Salar Ali; Zakir Hussain; Syed Hammad Ali; Shaukat Ali; Muhammad Younis Khan (Journal of Mountain Science, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Exploring the role of HaTIPs genes in enhancing drought tolerance in sunflower - Tania Safdar; Muhammad Hammad Nadeem Tahir; Zulfiqar Ali; Muhammad Habib ur Rahman (Molecular Biology Reports, 2023)

Bio-fortification of Two Wheat Cultivars with Iron and Zinc Through Their Soil and Foliar Application in Salt-Factored Soil: Growth, Ionic, Physiological, and Biochemical Modifications - Tayyaba Naz; Muhammad Mazhar Iqbal; Shah Fahad; Javaid Akhtar; Muhammad Saqib; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; et al. (Journal of Plant Growth Regulation, 2023)

Green investment, institutional quality, and environmental performance: evidence from G-7 countries using panel NARDL approach - Jiguo Zhao; Saif ur Rahman; Sahar Afshan; Muhammad Sibt E. Ali; Hammad Ashfaq; Sadia Idrees (Environmental Science and Pollution Research, 2023)

Antioxidant effects of zinc-oxide nanoparticles on post-thaw quality and in vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Habib Rehman; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Nisar Ahmad; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman (Small Ruminant Research, 2023)

Phytochemical, biological, and in-silico analysis of Colutea armata Hemsl. & Lace: A possible source of bioactive natural compounds - Ayisha Khalid; Samina Afzal; Farhan Abbas; Iftikhar Afzal; Muhammad Iqbal; Sarfraz Ahmad; Siddique Akber Ansari; Hamad M. Alkahtani; Tahir Ali Chohan; Umair Khurshid; Hammad Saleem; Carlos Leonardo Cespedes-Acuna (South African Journal of Botany, 2023)

Inclusiveness in Food Data Sets: Development of a Food Composition Dataset for South Asian Recipes With Focus on Pakistan - Muhammad Hammad Maqdoom; Syeda Areesha Najam; Shalin Ali; Sana Fatima; Alisha Momin; Abdul Samad; Humaira Jamshed (Journal of Nutrition Education and Behavior, 2023)

A comprehensive review on the botany, traditional uses, phytochemistry, pharmacology and toxicity of Anagallis arvensis (L).: A wild edible medicinal food plant - Hammad Saleem; Umair Khurshid; Muhammad Imran Tousif; Sirajudheen Anwar; Nasser A. Awadh Ali; Mohamad Fawzi Mahomoodally; Nafees Ahemad (Food Bioscience, 2023)

Sedimentological and Petrographical Characterization of the Cambrian Abbottabad Formation in Kamsar Section, Muzaffarabad Area: Implications for Proto-Tethys Ocean Evolution - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Tariq Mehmood; Khawaja Umair Majeed (Journal of Marine Science and Engineering, 2023)
The current sedimentological and petrographical research of the Abbottabad Formation has been carried out in order to understand the formation and evolution of the Proto-Tethys Ocean during the Cambrian on the northern margin of the Indian Plate. The Muzaffarabad region is located east of the Upper Indus Basin and the southern part of the Hazara Kashmir Syntaxis. The geological history of the region varies from the Precambrian to the recent period. The Cambrian Abbottabad Formation is well exposed along the Hazara Kashmir Syntaxis at the core of the 500-m-thick Muzaffarabad anticline. The Abbottabad Formation is an unconformity-bounded allo-stratigraphic unit. It has an unconformable lower contact with the Late Precambrian Dogra Formation and an unconformable upper contact with the Paleocene Hangu Formation. The Abbottabad Formation has been divided into four lithofacies, from bottom to top, namely, thinly interbedded dolomite and shale, cherty-stromatolitic dolomite, oxidized limonitic-brecciated zone, and quartzite, with significant lithological changes. Petrographic studies revealed four types of dolomites: fine crystalline dolomite (Dol. I), dolomitic cryptocrystalline chert (Dol. II), algal mat-stromatolitic dolomite (Dol. III), and intraclastic-dolo-grain stone (Dol. IV). The mineral composition of dolostone was analyzed using X-ray diffraction (XRD) and found to be consistent with previous petrographic studies. The dolomite mineral content decreased from base to top, while chert increased towards the top. Elemental weight percentages through energy dispersive X-ray (EDX) analysis show different elements constitute the minerals found in the dolostone, as confirmed by petrographic and XRD analysis. Using outcrop data, facies information, and geochemical data, a modified depositional model of the Abbottabad Formation was developed. During the Early Cambrian period, the formation was deposited in a shallow subtidal to supratidal setting of the Proto-Tethys Ocean. The top of this deposit marks the Cambrian–Paleocene boundary. Because of the progressively coarsening outcrop sequences, this formation seems to be at the very top of the Proto-Tethys Ocean’s shallow marine system.

Zeolite amendment reduces lead accumulation and improves growth and yield in tomato plants irrigated with sewage water - Rashid Jawad; Aamir Nawaz; Shaghef Ejaz; Sajid Ali; Muhammad Shahzad Saleem; Hafiz Mohkum Hammad (Environmental Science and Pollution Research, 2023)

Novel modeling and optimization framework for Navy Blue adsorption onto eco-friendly magnetic geopolymer composite - Hammad Khan; Sajjad Hussain; Rehman Zahoor; Muhammad Arshad; Muhammad Umar; Mohsin Ali Marwat; Adnan Khan; Javaid Rabbani Khan; Muhammad Abdul Haleem (Environmental Research, 2023)

Leaf rolling dynamics for atmospheric moisture harvesting in wheat plant as an adaptation to arid environments - Sabah Merrium; Zulfiqar Ali; Muhammad Hammad Nadeem Tahir; Muhammad Habib-ur-Rahman; Sadia Hakeem (Environmental Science and Pollution Research, 2022)
Plant species surviving in the arid regions have developed novel leaf features to harvest atmospheric water. Before the collected water evaporates, it is absorbed and transported for storage within the tissues and move toward the root zone through the unique chemistry of leaf structures. Deep insights into such features reveal that similarities can be found in the wheat plant. Therefore, this study aimed to evaluate the leaf rolling dynamics among wheat genotypes and their relationships with moisture harvesting and its movement on the leaf surface. For this purpose, genotypes were characterized for leaf rolling at three distinct growth stages (tillering, booting, and spike emergence). The contact angle of leaf surface dynamics (adaxial and abaxial), water budget, and morphophysiological traits of genotypes were measured. The results indicate that leaf rolling varies from inward to twisting type among genotypes and positively affected the water use efficiency and soil moisture difference at all growth stages under normal and drought conditions. Results of wetting property (hydrophilic < 90°) of the leaf surface were positively associated with the atmospheric water collection (4–7 ml). The lower values of contact angle hysteresis (12–19°) also support this mechanism. Thus, genotypes with leaf rolling dynamics (inward rolled and twisted) and surface wettability is an efficient fog harvesting system in wheat for interception and utilization of fog water in drought-prone areas. These results can be exploited to develop self-irrigated and drought-tolerant crops.

Exploring the potential effect of Achnatherum splendens L.–derived biochar treated with phosphoric acid on bioavailability of cadmium and wheat growth in contaminated soil - Muhammad Irfan; Khadim Dawar; Shah Fahad; Imran Mehmood; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2022)

Depositional Sedimentary Facies, Stratigraphic Control, Paleoecological Constraints, and Paleogeographic Reconstruction of Late Permian Chhidru Formation (Western Salt Range, Pakistan) - Syed Kamran Ali; Hammad Tariq Janjuhah; Syed Muzyan Shahzad; George Kontakiotis; Muhammad Hussain Saleem; Usman Khan; Stergios D. Zarkogiannis; Panayota Makri; Assimina Antonarakou (Journal of Marine Science and Engineering, 2021)
The Upper Indus Basin, in Pakistan’s western Salt Range, is home to the Zaluch Gorge. The sedimentary rocks found in this Gorge, belonging to the Chhidru Formation, were studied in terms of sedimentology and stratigraphy, and provide new insights into the basin paleogeographic evolution from the Precambrian to the Jurassic period. Facies analysis in the Chhidru Formation deposits allowed the recognition of three lithofacies (the limestone facies—CF1, the limestone with clay interbeds facies—CF2, and the sandy limestone facies—CF3) with five microfacies types (mudstone biomicrite—MF-1, wackestone-biomicrite—MF-2, wackestone-biosparite—MF-3, pack-stone-biomicrite—MF-4, and packstone-biosparite—MF-5), as well as their depositional characteristics. The identified carbonate and siliciclastic formations display various facies in a shallow marine environment, with different lithologies, sedimentary features, and energy conditions. It is thought that the depositional characteristics of these microfacies are closer to those of the middle to outer shelf. Because of the progressively coarsening outcrop sequence, this formation seems to be at the very top of the high stand system tract (HST). A modified dynamic depositional model of the Chhidru Formation is further built using outcrop data, facies information, and stratigraphy. According to this concept, the formation was deposited in the middle to inner shelf area of the shallow marine environment, during the Late-Permian period. The Permo-Triassic Boundary (PTB), which is the end of the type-1 series, is marked by this formation’s top.

Hydrogen Sulfide: A Novel Gaseous Molecule for Plant Adaptation to Stress - Mukhtar Ahmed; Shah Fahad; Muhammad Arif Ali; Sajjad Hussain; Muhammad Tariq; Fariha Ilyas; Shakeel Ahmad; Shah Saud; Hafiz Mohkum Hammad; Wajid Nasim; Chao Wu; Hongyan Liu (Journal of Plant Growth Regulation, 2021)

Photocatalytic degradation of crystal violet dye under sunlight by chitosan-encapsulated ternary metal selenide microspheres - Waqar Ahmad; Adnan Khan; Nisar Ali; Sana Khan; Salah Uddin; Sumeet Malik; Nauman Ali; Hamayun Khan; Hammad Khan; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Spatial modeling of Dengue prevalence and kriging prediction of Dengue outbreak in Khyber Pakhtunkhwa (Pakistan) using presence only data - Hammad Ahmad; Asad Ali; Syeda Hira Fatima; Farrah Zaidi; Muhammad Khisroon; Syed Basit Rasheed; Ihsan Ullah; Saleem Ullah; Muhammad Shakir (Stochastic Environmental Research and Risk Assessment, 2020)

Ecophysiological response of early stage Albizia lebbeck to cadmium toxicity and biochar addition - Muhammad Talha Bin Yousaf; Muhammad Farrakh Nawaz; Hammad Fayyaz Khawaja; Sadaf Gul; Shafaqat Ali; Irfan Ahmad; Fahd Rasul; Muhammad Rizwan (Arabian Journal of Geosciences, 2019)

Concurrent vaccination of goats with foot and mouth disease (FMD) and peste des petits ruminants (PPR) booster vaccines - Muhammad Khalid Mansoor; Abdullmajeed Hamood Al-Rawahi; Hatim Ali El-Tahir; Badar Al-Faraei; Muhammad Hammad Hussain; Muhammad Nadeem Asi; Ibrahim Al-Hussani; Safwat Sabar (Tropical Animal Health and Production, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)